COL1A1 novel splice variant in osteogenesis imperfecta and splicing variants review: A case report - Dirani, Michella; Cuenca, Victor D.; Romero, Vanessa I. (Frontiers in Surgery, 2022)
Background Osteogenesis imperfecta (OI) is a rare heterogeneous genetic disorder commonly autosomal dominant with variants in the COL1A1 and COL1A2 genes. It is characterized by bone fragility and deformity, recurrent fractures, blue sclera, dentinogenesis imperfecta, short stature, and progressive deafness. Case presentation We present a novel splicing mutation in the COL1A1 gene (c.2398-1G > C) in a 6-year-old Ecuadorian girl with fractures after light pressure and blue sclera. We identified the pathogenic variant, performed a literature review of splice variants, and recognized their location in the COL1A1 functional domains. Conclusion We describe the first clinical description of a patient with OI type 1 caused by a splice variant in intron 34 of COL1A1 gene and identify that most of them are localized in the triple-helical region domain. We suggest that the splice variant in signal peptide, von Willebrand factor type C, and nonhelical regions maintain their functionality or that individuals affected with severe cases die early in development and are not reported.